Hepatosplenic T Cell Lymphoma Involved Small Vessels of Central Nervous System (2020)
ABSTRACT: Hepatosplenic T-cell lymphoma (HSTCL) is a rare, aggressive type of peripheral T – cell lymphoma characterized by infiltration and proliferation of atypical T-cells within the sinusoids of the spleen, liver, and bone marrow. This case report consists of a young male, who was admitted to a local hospital with a history of unexplained fever, odynophagia, and rash, initially mimicking infectious disease. The patient died due to multiorgan failure and the correct diagnosis only was accomplished in the autopsy. This case highlights the difficulty of diagnosing HSTCL and the necessity of considering it in patients with unknown origin fever with hyperferritinemia.